Análise da modelagem matemática sobre a secagem de alumina em leito fixo espesso - Mello, Mateus Araújo de (Universidade Federal de São Carlos, 2022)
The fixed bed is widely applied, studied and reported in the literature. From the stuffing towers found in the chemical industry to the modern fixed beds with membranes used in the production of hydrogen, many were the contributions to reach the state of the art of this type of reactor. Fixed bed drying, in which the bed of particles remains stationary while the air percolates through the porous medium, yielding heat and absorbing moisture, is more used when dealing with impact-sensitive grains, even so, on a small scale. However, knowledge about fixed bed drying processes can be extended to conveyor belt dryers, in addition to storage silos, with regard to dynamic behavior. Unlike drying with bed movement, fixed bed drying accentuates the temperature and humidity gradients of the particles, and this non-uniformity is a generally undesired effect. The Final Paper proposal summarized here aims to simulate a dynamic model of alumina drying in a fixed bed, varying both typical operating conditions and bed dimensions. Numerical tests will then be carried out using a MatLab program developed in the Particulate Systems area of DEQ/UFSCar. With the results of the simulations it is intended to identify trends of change in the magnitude of the internal gradients in face of the variations made in the program.
Analysis of mathematical modeling on the drying of alumina in a thick fixed bed
Keywords: Secagem; Leito fixo; Drying; Fixed bed; ENGENHARIAS::ENGENHARIA QUIMICA